2012
DOI: 10.1002/lt.23542
|View full text |Cite
|
Sign up to set email alerts
|

Telaprevir‐based triple therapy in liver transplant patients with hepatitis C virus: A 12‐week pilot study providing safety and efficacy data

Abstract: After liver transplantation (LT), the management of recurrent hepatitis C virus (HCV) infections still remains a major challenge. In HCV genotype 1 patients not undergoing transplantation, the introduction of protease inhibitor (PI)-based regimens has increased the sustained virological response rate significantly. This pilot study investigated both the safety and efficacy of telaprevir (TVR)-based triple therapy in HCV-infected LT patients with a special emphasis on drug-drug interactions between immunosuppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2
2

Year Published

2013
2013
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 30 publications
2
48
2
2
Order By: Relevance
“…In contrast to several Western reports of the triple therapy demonstrating moderate success for genotype 1 recurrent hepatitis C after DDLT (3,15,16), the present results were discouraging, with an end-of-treatment response rate of only 25% (2/8). It is important to note, however, that all eight recipients indicated for the triple therapy in our study had been resistant to standard dual treatment with PEG-IFN and RBV.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to several Western reports of the triple therapy demonstrating moderate success for genotype 1 recurrent hepatitis C after DDLT (3,15,16), the present results were discouraging, with an end-of-treatment response rate of only 25% (2/8). It is important to note, however, that all eight recipients indicated for the triple therapy in our study had been resistant to standard dual treatment with PEG-IFN and RBV.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, however, only 25% (2/8) of patients achieved HCV-negative status at the end of therapy. Accumulating reports from Western countries in a DDLT setting suggest the efficacy of triple therapy for recurrent hepatitis C with genotype 1b (3,15,16), but the present results demonstrated dismal results for non-responders to standard dual therapy. Documented drug-drug interactions with protease inhibitors have raised concerns about the safety of protease inhibitors in the post-transplant setting.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…1 Protease inhibitor-based regimens improve the virological response in nontransplant patients with HCV genotype 1. In a previous issue of Liver Transplantation, Werner et al 2 demonstrated the safety and efficacy of telaprevir-based triple therapy in liver transplant patients with HCV. Boceprevir with a calcineurin inhibitor (CNI) seems to require a lower dose reduction than telaprevir.…”
Section: To the Editorsmentioning
confidence: 99%